A Promising Antifungal and Antiamoebic Effect of Silver Nanorings, a Novel Type of AgNP - Sara González-Fernández; Victor Lozano-Iturbe; Mª Fe Menéndez; Helena Ordiales; Iván Fernández-Vega; Jesús Merayo; Fernando Vazquez; Luis M. Quirós; Carla Martín (MDPI AG, 2022)
Silver nanoparticles (AgNPs) play an important role in the medical field due to their potent antimicrobial activity. This, together with the constant emergence of resistance to antimicrobial drugs, means AgNPs are often investigated as an alternative to solve this problem. In this article, we analyzed the antifungal and antiamoebic effects of a recently described type of AgNP, silver nanorings (AgNRs), and compared them with other types of AgNPs. Tests of the activity of AgNPs against various fungal and amoebic species were carried out. In all cases, AgNPs showed a high biocidal effect, although with fungi this depended on the species involved. Antifungal activity was detected by the conditioning of culture media or water but this effect was not dependent on the release of Ag ions. On the other hand, the proliferation of Acanthamoeba castellanii trophozoites was reduced by silver nanorings (AgNRs) and silver nanowires (AgNWs), with AgNWs being capable of totally inhibiting the germination of A. castellanii cysts. AgNRs constitute a new type of AgNP with an antifungal and antiacanthamoebic activity. These results open the door to new and effective antimicrobial therapies as an alternative to the use of antifungals or antiamoebic drugs, thus avoiding the constant appearance of resistance and the difficulty of eradicating infections.